Long term outcome of single ventricle physiology with pulmonary restriction not undergoing Fontan repair. (25th November 2020) - Buendia, F; Ramirez, B; Gallego, P; Oliver, J.M; Montserrat, S; Osa, A; Miranda, B; Rodriguez Puras, M.J; Gonzalez, A.E; Carbonell, B; Meras, P; Adsuar, A; et al.
Abstract: Background: Patients with univentricular physiology who do not complete the palliation to Fontan are a heterogeneous group with unknown long term outcome. Aims: This study aimed at describing the clinical course and long-term survival of patients with SV physiology with restricted pulmonary flow that had not undergone a Fontan type of repair. Methods: From the prospectively maintained databases of the adult congenital cardiac units of five tertiary referral centers, data from all SV physiology patients were obtained. Patients completing a Fontan type palliation or developing Eisenmenger physiology and segmental pulmonary hypertension were excluded. Baseline data were recorded on the first visit at adult congenital heart disease (ACHD) unit. The primary end point was death. Results: 101 patients (50.5% females) were identified. Mean age at end of follow up was 39.3±11.3 years. Of these, 45 (44.6%) were unoperated (group 1, restricted forward pulmonary flow with or without pulmonary banding), 38 (37.6%) had undergone a cavopulmonary shunt as a definitive palliation (group 2) and 18 (17.8%) had aortopulmonary shunts (group 3). The main diagnosis was double inlet left ventricle (DILV) (N: 52, 51.5%) and most of the ventricle was left (82.2%). The principal reason for not performing a Fontan repair was mean pulmonary artery pressure >18 mmHg. At initial visit at the ACHD unit patients were 32.2±11.1 years of age. 35% of the patients were in NYHA class III-IV, with no differences between groups. However, patients in group 2 had worse oxygen saturation (p=002) and higher haemoglobin (p=0.037). After a mean follow-up of 7.3±4.1 years, mortality was 20.8% (21 patients), being sudden death (7p, 6.9%) the most frequent cause. Patients in group 3 showed worse ventricular function (p=0.0001) and a trend to higher mortality that did not reach statistical significance (HR 2.7, CI 95% 0.91–8.14, P=0.07). Conclusions: Patients with single ventricle physiology not undergoing Fontan repair are a population of high risk, with sudden death as main driver of mortality. Patients palliated with aortopulmonary shunts are prone to worse ventricular function and a trend to higher mortality. Funding Acknowledgement: Type of funding source: Public hospital(s)